An exercise in nostalgia: Nostalgia promotes health optimism and physical activity. Issue 10 (2nd October 2016) - Kersten, Mike; Cox, Cathy R.; Van Enkevort, Erin A.
Abstract : Objective : Previous research has shown that nostalgia, a sentimental longing for the past, leads to greater feelings of optimism, with other work demonstrating that optimistic thinking (general & health-orientated) is associated with better physical and psychological health. Integrating these two lines of research, the current studies examined whether nostalgia-induced health optimism promotes attitudes and behaviours associated with better physical well-being. Methods : Participants, in three experiments, were randomly assigned to write about either a nostalgic or ordinary event. Following this, everyone completed a measure of health optimism (Studies 1–3), measures of health attitudes (Study 2) and had their physical activity monitored over the course of 2 weeks (Study 3). Results : The results revealed that, in comparison to control conditions, nostalgic reverie led to greater health optimism (Studies 1–3). Further, heightened health optimism following nostalgic reflection led to more positive health attitudes (Study 2), and increased physical activity over a two-week period (i.e. Fitbit activity trackers; Study 3). Conclusions : These findings highlight the importance of nostalgia on health attitudes and behaviours. Specifically, this work suggests that nostalgia can be used as a mechanism to increase the importance, perceived efficacy and behaviour associated with better physical health.